The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12968-019-0572-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased rotational flow and circumferential wall shear stress as early markers of descending aorta dilation in Marfan syndrome: a 4D flow CMR study

Abstract: BackgroundDiseases of the descending aorta have emerged as a clinical issue in Marfan syndrome following improvements in proximal aorta surgical treatment and the consequent increase in life expectancy. Although a role for hemodynamic alterations in the etiology of descending aorta disease in Marfan patients has been suggested, whether flow characteristics may be useful as early markers remains to be determined.MethodsSeventy-five Marfan patients and 48 healthy subjects were prospectively enrolled. In- and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
(48 reference statements)
0
24
0
1
Order By: Relevance
“… 17 In this context, it is important to underline that flow in the aortic arch is impacted by aortic curvature and the presence of supra-aortic trunks. 28 , 32 These characteristics may promote local recirculation zones, 33 , 34 thus creating regions of low and oscillatory WSS 12 , 32 that may contribute to aortic arch aneurysm formation. 28 However, considering our results and previous investigations, we conclude that there is not sufficient evidence to support the contribution of this mechanism to aortic dilation in patients with BAV.…”
Section: Discussionmentioning
confidence: 99%
“… 17 In this context, it is important to underline that flow in the aortic arch is impacted by aortic curvature and the presence of supra-aortic trunks. 28 , 32 These characteristics may promote local recirculation zones, 33 , 34 thus creating regions of low and oscillatory WSS 12 , 32 that may contribute to aortic arch aneurysm formation. 28 However, considering our results and previous investigations, we conclude that there is not sufficient evidence to support the contribution of this mechanism to aortic dilation in patients with BAV.…”
Section: Discussionmentioning
confidence: 99%
“…Altered flow patterns and decreased circumferential WSS have been reported in Marfan patients as well [ 22 , 43 ]. The maps of abnormally directed hemodynamics may have added value in diagnosis, timing of surgery and patient monitoring in the Marfan population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since vascular disease is promoted by low and oscillatory WSS [ 25 , 26 ], the multidirectionality of WSS has been extensively investigated by comparison with the curvature of the aorta [ 19 , 22 , 27 ]. However, the comparison of pathological axial and circumferential WSS with the normal situation may be confounded by an altered aortic shape in BAV disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This research was based mainly on CMR since this imaging technique is widely used in the clinical management of these patients. Most studies reported increased stiffness in MFS patients, either as reduced distensibility [26,[57][58][59][60][61] or longitudinal aortic strain [9], or as an increase in PWV [26,59,60,62]. However, despite the relatively large number of cross-sectional studies available, only two longitudinal CMR studies evaluated the potential predictive role of increased aortic stiffness in aortic dilation or aortic events in MFS patients.…”
Section: Magnetic Resonance Imaging In Marfan Syndrome Patientsmentioning
confidence: 99%